PENGEMBANGAN LEMBAR KEGIATAN SISWA BERORIENTASI PENEMUAN TERBIMBING (GUIDED DISCOVERY) UNTUK SMA KELAS X PADA MATERI FUNGI - ROCHMAWATI, ELY (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Development of worksheet feasibility of worksheets on fungi and describe learning outcomes of students with worksheets that fungi developed on the material, and describe the students of response to the teaching and learning activities. This research is the development of worksheets using 4-D model (four D models). Model development include of 4 steps of the define, design, development and desseminate. Steps this research to the development. The research was conducted at the Madrasah Aliyah Sidoarjo in class X. The result has shown that worksheets are included in the criteria developed very decent. The results of student responses showedÂ  positive response to the developed LKS language, and physical presentation. Student learning outcomes after the use the worksheet stated that 2 of the 15 students declared incomplete. Key words: development of teaching materials, guided discovery, fungi